CHARACTERIZATION, ANTIMICROBIAL, AND METABOLIC ACTIVITY OF GREEN AND CHEMICALLY SYNTHESIZED ZINC OXIDE NANOPARTICLES - SUMATHI S; BANUPRIYA SJS; AKHILA V; PADMA PR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The aim of the present study is a synthesis of zinc oxide nanoparticles (ZnONPs) by green and chemical method. The nanoparticles were tested for their antimicrobial, antibiofilm activity, biocompatibility, and hemolysis activity. Methods: We have synthesized ZnONPs both by green and chemical synthesis using the coprecipitation method. To understand the functional group, absorbance, crystalline nature, size, and shape of the synthesized particles, Fourier transform infrared (FTIR), ultraviolet–visible spectroscopy, X-ray diffraction, and scanning electron microscopy were done. Antibacterial activity was carried out using different bacterial strains. The cytotoxicity of synthesized nanoparticles was checked using MTT assay with Klebsiella pneumoniae. Antibiofilm activities of both synthesized nanoparticles were done using Staphylococcus aureus and to assess the toxicity of nanoparticles at the cellular level, hemolysis assay was performed. Results: The yield of nanoparticles in green synthesis was much higher when compared to chemical synthesis. Spectral results showed that the synthesized nanoparticles were ZnONPs. Antibacterial, antibiofilm, and hemolysis assay showed that green nanoparticles were more potent than chemical nanoparticles. Conclusion: Hence, green synthesis provides an advantage over chemical synthesis as it is cost effective, environmentally friendly, and easily scaled up for large-scale synthesis.